Association of Angiotensin-Converting Enzyme Inhibitors and Angiotensin II Blockers With Severity of COVID-19: A Multicenter, Prospective Study. (May 2021) - Hakeam, Hakeam A.; Alsemari, Muhannad; Duhailib, Zainab Al; Ghonem, Leen; Alharbi, Saad A.; Almutairy, Eid; Sheraim, Nader M. Bin; Alsalhi, Meshal; Alhijji, Ali; AlQahtani, Sara; Khalid, Mohammed; Barry, Mazin
Background: Speculations whether treatment with angiotensin-converting enzyme inhibitors (ACE-I) or angiotensin II receptor blockers (ARB) predisposes to severe coronavirus disease 2019 (COVID-19) or worsens its outcomes. This study assessed the association of ACE-I/ARB therapy with the development of severe COVID-19. Methods: This multi-center, prospective study enrolled patients hospitalized for COVID-19 and receiving one or more antihypertensive agents to manage either hypertension or cardiovascular disease. ACE-I/ARB therapy associations with severe COVID-19 on the day of hospitalization, intensive care unit (ICU) admission, mechanical ventilation and in-hospital death on follow-up were tested using a multivariate logistic regression model adjusted for age, obesity, and chronic illnesses. The composite outcome of mechanical ventilation and death was examined using the adjusted Cox multivariate regression model. Results: Of 338 enrolled patients, 245 (72.4%) were using ACE-I/ARB on the day of hospital admission, and 197 continued ACE-I/ARB therapy during hospitalization. Ninety-eight (29%) patients had a severe COVID-19, which was not significantly associated with the use of ACE-I/ARB (OR 1.17, 95% CI 0.66-2.09; P = .57). Prehospitalization ACE-I/ARB therapy was not associated with ICU admission, mechanical ventilation, or in-hospital death. Continuing ACE-I/ARB therapy during hospitalization was associated with decreased mortality (OR 0.22, 95% CI 0.073-0.67; P = .008). ACE-I/ARB use was not associated with developing the composite outcome of mechanical ventilation and in-hospital death (HR 0.95, 95% CI 0.51-1.78; P = .87) versus not using ACE-I/ARB. Conclusion: Patients with hypertension or cardiovascular diseases receiving ACE-I/ARB therapy are not at increased risk for severe COVID-19 on admission to the hospital. ICU admission, mechanical ventilation, and mortality are not associated with ACE-I/ARB therapy. Maintaining ACE-I/ARB therapy during hospitalization for COVID-19 lowers the likelihood of death. Clinical Trial Registration: ClinicalTrials.gov, NCT4357535.